The Relationship between Vascular Elasticity and Cognitive Function in Medical Students - Mochammad Nafi Al Munthoharri; Nurfitri Bustamam; Maulidya Ayudika Dandanah; Marlina Dewiastuti (JURNAL INFO KESEHATAN, 2026)
Vascular stiffness is a known risk factor for cognitive impairment, particularly in the elderly. However, its impact on younger populations, such as medical students, remains less explored. Early subtle changes in vascular health may affect cognitive domains necessary for academic performance. This study aimed to examine the relationship between vascular elasticity and cognitive function in medical students. A cross-sectional study design was conducted using simple random sampling. Cognitive function was assessed using the Mini-Mental State Examination (MMSE), Digit Symbol Substitution Test (DSST), and Digit Span Test (DST). Vascular elasticity was measured using the SA-3000P accelerated photoplethysmography analyzer and categorized as suboptimal, normal, or optimal. The sample size was 51 subjects who met the following criteria: non-smokers with low to moderate stress levels, and no history of head trauma, brain haemorrhage, narcotics use, diabetes mellitus, or hypertension. The Mann-Whitney test revealed a significant difference in MMSE scores between groups with different levels of vascular elasticity (p = 0.042).  The Chi-square test also revealed a significant difference in DSST between groups with different levels of vascular elasticity (p = 0.023; PR = 6.667; CI = 0.969 - 45.857). However, no significant difference was found in DST scores (p = 0.072). In conclusion, this study found a significant relationship between vascular elasticity and cognitive function in medical students, suggesting that early vascular changes may influence cognitive function even in young, healthy individuals.